Detection and quantification of Plasmodium falciparum in human blood by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry: a proof of concept study - Stauning, Marius Ahm; Jensen, Christian Salgård; Staalsøe, Trine; Kurtzhals, Jørgen A. L. (Malaria journal, 2023)
Background Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF) has revolutionized identification of bacteria and is becoming available in an increasing number of laboratories in malaria-endemic countries. The purpose of this proof-of-concept study was to explore the potential of MALDI-TOF as a diagnostic tool for direct detection and quantification of Plasmodium falciparum in human blood. Methods Three different P. falciparum strains (3D7, HB3 and IT4) were cultured and synchronized following standard protocols. Ring-stages were diluted in fresh blood group 0 blood drawn in EDTA from healthy subjects to mimic clinical samples. Samples were treated with saponin and washed in PBS to concentrate protein material. Samples were analysed using a Microflex LT MALDI-TOF and resulting mass spectra were compared using FlexAnalysis software. Results More than 10 peaks specific for P. falciparum were identified. The identified peaks were consistent among the three genetically unrelated strains. Identification was possible in clinically relevant concentrations of 0.1% infected red blood cells, and a close relationship between peak intensity and the percentage of infected red blood cells was seen. Conclusion The findings indicate that the method has the potential to detect and quantify P. falciparum at clinically relevant infection intensities and provides proof-of-concept for MALDI-TOF-based diagnosis of human malaria. Further research is needed to include other Plasmodium spp., wildtype parasite isolates and to increase sensitivity. MALDI-TOF may be a useful tool for mass-screening purposes and for diagnosis of malaria in settings where it is readily available.